Keseimbangan Pola Jiwa dsn Pola Pikir dalam Kepribadian Manusia - Najwa Fibi Khamidiyah; Miftarah Ainul Mufid; Ahmad Zainuddin (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Human personality is a complex thing and is formed from various internal and external factors that interact with each other in a complex way. One way to understand personality is to observe the relationship between a person's soul pattern and mindset. This study aims to investigate how these patterns are interrelated in shaping character and behavior through a thematic interpretation approach. This research is a qualitative research with the Tafsir Maudhu'i research model that analyzes Qur'anic verses related to the soul and mind. This study shows that achieving a balance between soul patterns and mindsets is essential for forming a stable and healthy personality. A well-managed soul pattern will support wise thinking in guiding the soul towards peace and maturity. This research provides new insights into the importance of integrating spiritual and rational aspects in forming a harmonious personality, as well as its implications for sel development and education.